The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1074/jbc.272.17.11426
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Active Mutant of the Mitogen-activated Protein Kinase Kinase MEK1 Induces Epithelial Dedifferentiation and Growth Inhibition in Madin-Darby Canine Kidney-C7 Cells

Abstract: Overexpression of a constitutively active mitogen-activated protein kinase kinase (MAPKK or MEK) induces neuronal differentiation in adrenal pheochromocytoma 12 cells but transformation in fibroblasts. In the present study, we used a constitutively active MAPK/extracellular signal-regulated kinase (ERK) kinase 1 (MEK1) mutant to investigate the function of the highly conserved MEK1-ERK2 signaling module in renal epithelial cell differentiation and proliferation. Stable expression of constitutively active MEK1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 28 publications
6
65
0
Order By: Relevance
“…The activation of ERK by EphA2 is transient, returning to basal levels within 45 -60 min. This timing of ERK activation is interesting in light of evidence that the duration of ERK signaling can profoundly impact the biological outcomes of receptor signaling (Aliaga et al, 1999;Brunet et al, 1995;Cowley et al, 1994;Roovers et al, 1999;Roovers and Assoian, 2000;Schramek et al, 1997). Based on these findings, we suggest that transient ERK activation could similarly inhibit tumor cell growth in response to EphA2 stimulation.…”
Section: Discussionmentioning
confidence: 53%
“…The activation of ERK by EphA2 is transient, returning to basal levels within 45 -60 min. This timing of ERK activation is interesting in light of evidence that the duration of ERK signaling can profoundly impact the biological outcomes of receptor signaling (Aliaga et al, 1999;Brunet et al, 1995;Cowley et al, 1994;Roovers et al, 1999;Roovers and Assoian, 2000;Schramek et al, 1997). Based on these findings, we suggest that transient ERK activation could similarly inhibit tumor cell growth in response to EphA2 stimulation.…”
Section: Discussionmentioning
confidence: 53%
“…7A). PD98059 has previously been shown to block the phosphorylation of ERK1 and ERK2 by constitutively active forms of MEK (30,31). The activation of p42 ERK /p44…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies by others showed that expression of a constitutively activated MEK1 induce in NIH3T3 cells morphological changes, anchorage-independent growth and accelerated S phase entry (Blalock et al, 2000;Brunet et al, 1994;Greulich and Erikson, 1998;Ljungdahl et al, 1998;Rimerman et al, 2000;Schramek et al, 1997), phenotypes similar to cells overexpressing MST4. Likewise, constitutively active ERK was shown to be su cient to elicit cell transformation (Greulich et al, 1996;Huang et al, 1999;Plattner et al, 1999;Verheijen et al, 1999).…”
Section: Discussionmentioning
confidence: 98%